2012
DOI: 10.1111/j.1523-536x.2012.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric Interventions for Low‐Risk Pregnant Women in France: Do Maternity Unit Characteristics Make a Difference?

Abstract: Background In many countries the closure of small maternity units has raised concerns about how the concentration of low‐risk pregnancies in large specialized units might affect the management of childbirth. We aimed to assess the role of maternity unit characteristics on obstetric intervention rates among low‐risk women in France. Methods Data on low‐risk deliveries came from the 2010 French National Perinatal Survey of a representative sample of births (n = 9,530). The maternity unit characteristics studied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
52
3
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(64 citation statements)
references
References 45 publications
5
52
3
4
Order By: Relevance
“…Our findings confirm that variations in intervention rates are not fully explained by the sociodemographic or clinical characteristics of women planning to give birth 10–12. While we did observe significant associations between OU size and midwifery staffing and some intervention rates, our results do not suggest that there is a straightforward or clear relationship between these factors13 14 and intervention rates, at least within the ranges observed within our sample. Our further exploratory analyses showed strong positive associations between intervention rates in ‘low-risk’ and ‘higher risk’ women planning birth in the same OU, which suggests that intervention rates may be affected by some institutional level factor, an ‘interventionist culture’, for example, or simply that the same influences on intervention rates apply to all births in any given setting.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…Our findings confirm that variations in intervention rates are not fully explained by the sociodemographic or clinical characteristics of women planning to give birth 10–12. While we did observe significant associations between OU size and midwifery staffing and some intervention rates, our results do not suggest that there is a straightforward or clear relationship between these factors13 14 and intervention rates, at least within the ranges observed within our sample. Our further exploratory analyses showed strong positive associations between intervention rates in ‘low-risk’ and ‘higher risk’ women planning birth in the same OU, which suggests that intervention rates may be affected by some institutional level factor, an ‘interventionist culture’, for example, or simply that the same influences on intervention rates apply to all births in any given setting.…”
Section: Discussioncontrasting
confidence: 93%
“…Previous studies have found some association between junior doctor staffing levels and intervention rates,13 and mixed or inconclusive results on the relationship between unit size or the level of neonatal care available and intervention rates 14–16. Studies in France and Australia suggest that smaller units may have lower rates of some interventions, but in these studies, smaller units differed from larger units in other ways including, for example, the level of obstetric and neonatal care available and rurality 14 26. Our findings confirm that variations in intervention rates are not fully explained by the sociodemographic or clinical characteristics of women planning to give birth 10–12.…”
Section: Discussionsupporting
confidence: 66%
“…The association between caesarean sections and private health care is well documented and occurs in developed and developing countries 2,3,4,5,6 . However, none of these countries has as high a caesarean section prevalence as that reported for the private sector in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the higher use of obstetric interventions and c-sections in women served by the private sections has been observed in a number of countries around the world, not only in Brazil 22,23,24 .…”
mentioning
confidence: 97%